Investigation of Heat Stepping Process for Epoxy-Amine Binders - Petro Stukhlyak; Andrii Mykytyshyn; Ihor Chykhira (Advances in Materials Science and Engineering)
It is determined that in order to create a protective coating with high physical, mechanical, and thermophysical characteristics, it is necessary to carry out the appropriate heat stepping during its formation. The relevance of such processing mode use providing the increase of physical-mechanical and operational characteristics of epoxy material coatings due to the structure-forming processes in the material is substantiated.